The Opportunity Implementation HIV Prevention Infection Program from Mother to Child in Bali - Giri, Ketut Espana; Nopiyani, Ni Made Sri; Merati, Tuti Parwati (Journal of Global Research in Public Health, 2018)
Women infected with HIV can transmit HIV from mother to child during pregnancy, childbirth and lactation. Implementation of programs to prevent HIV transmission from mother to child (PPIA) in Bangli not been implemented optimally. The study was conducted to determine the chances of program implementation PPIA, faced viewed from the perspective of users and service providers. The study is a qualitative case study approach. Collecting data with in-depth interviews using interview guide to users and service providers. Informants were selected purposively as many as 18 people of 10 pregnant women, two counselors, two laboratory workers, 2 heads of health centers, 1 holder of program P2, and 1 Sekretais KPA Bangli regency. Data collection was conducted April-May 2016 in Puskesmas Losses Tembuku I and II health center in Bangli regency. Analysis of data using thematic analysis. Opportunities from service users say that husbands and health professionals strongly support pregnant women to take the test. Service providers revealed no support from the public, especially health workers and community leaders in collecting pregnant women.Opportunities users is the support of their husbands and health professionals, while opportunities are providers of community support and cooperation within the team